Problems of forming infrastructure support for innovative activities of construction enterprises. - Gazukin, A. (Ways to Improve Construction Efficiency, 2022)
The article analyzes key issues in the formation of infrastructure support for innovative activities of construction enterprises in Ukraine. The main barriers hindering the technological modernization of the industry are systematized and classified into five interrelated areas: financial and economic, organizational and managerial, legal, human resources, and informational. It is established that the role of infrastructure support is to create conditions for the effective transformation of scientific developments into a competitive construction product. Its functioning is a necessary prerequisite for increasing the competitiveness of enterprises, stimulating long-term innovative development, and modernizing the economy as a whole. The lack of an effective infrastructure hinders the implementation of new technologies, materials, and management solutions. The analysis of the authors' works emphasized the complex nature of the identified problems, which requires a systemic approach to their solution. The importance of harmonizing the regulatory framework with European standards, developing public-private partnership mechanisms, improving the education system, and creating modern digital platforms for information exchange is highlighted. Special attention is paid to the impact of the full-scale war, which, on the one hand, exacerbated existing problems (shortage of financial and human resources, destruction of the production base), and on the other hand, stimulated the search for unconventional solutions, such as modular technologies and 3D printing. The study revealed a number of systemic dysfunctions: from limited access to long-term financing and outdated building codes to a shortage of qualified specialists and significant information asymmetry between market participants. To overcome them, the creation of a comprehensive innovation infrastructure is proposed, the central link of which should be a state institution with advanced IT support for the accumulation and dissemination of information about innovative developments, which will contribute to their effective commercialization.